Ziarah Makam di Mbah Priok: Dinamika Tradisi Keagamaan dalam Efeknya terhadap Perubahan Sosial Ekonomi Masyarakat Setempat - Nurainun; Muhamad Ridwan Effendi (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2025)
Abstract The tradition of grave pilgrimage is an integral part of religious life in Indonesia, reflecting spiritual values while influencing social and economic dynamics. The Mbah Priok grave in North Jakarta serves as a symbol of cultural and spiritual heritage, attracting pilgrims from diverse backgrounds. However, modernization and socio-economic changes pose challenges to maintaining the relevance of this tradition. This study aims to uncover the role of the Mbah Priok grave in preserving religious traditions and highlighting its impact on the social and economic aspects of the local community. The primary objective is to identify the grave's role as a center for religious practices or traditions and its influence on the surrounding community. This research employs a qualitative. Data were collected through participatory observation, in-depth interviews, and documentation, utilizing instruments such as interview guides, field notes, and recording devices. Sampling techniques involved purposive sampling, which was further developed using snowball sampling. The findings reveal that the tradition of pilgrimage to Mbah Priok strengthens social values such as cooperation and solidarity, enhances adherence to religious norms, and creates new economic opportunities through local trade activities. The conclusion highlights the importance of balanced strategies for preserving traditions alongside modern developments, ensuring this tradition remains a significant part of the cultural and spiritual identity of the community.